Performance of vertical steel plate anchor in layered cohesionless soil - Alireza Parsa; Hamed Niroumand (Scientific Reports)
Abstract This study investigated the performance of steel vertical anchor plates in multi-layered cohesionless soils. The research evaluated the effects of various parameters, such as soil density, number of layers, and anchor embedment depth, on the pullout capacity of the anchors. For the research, a container with the dimensions of was filled with sand at two different densities (dense and loose) up to a height of 80 cm. The study used steel plate anchor. Plate anchor underwent 12 tests with different embedment depths. In this research, steel plate anchors with equal dimensions of 150 × 50 × 8 mm, with L/d ratios of 1–4 and H/d ratios of 1–4 were used. The research showed that increasing the distance of the steel anchor from the soil wall increased the pullout force. For example, embedding a steel anchor at a depth of tripled the pullout force. Finally, the study indicated that soil parameters and anchor embedment geometry directly influenced the pullout behavior of the anchors.